Karakterisasi Durian (Durio zibenthinus) Ngrambe di Jawa Timur, Indonesia - Endang Yuniastuti; Nandariyah Nandariyah; Samuel Reza Bukka (Universitas Sebelas Maret, 2018)
Durian is a tropical plant which can easily be found in South East Asia country such as Indonesian. Ngrambe village which it is located on Ngawi regency is one of central durian in East of Java. This research aimed to obtain data related to quantity and variety of superior local durian based on the morphological character. This study was conducted at Giriharjo, Ngrambe, Ngawi from October 2015 to January 2016. Based on the field survey, it was found that there are 60 varieties consist of 36 local durians, 9 superior released durians, and 15 introduction durians. By selection process among 60 varieties durian, there was found that 6 of local durians was potential as a superior character to be released as new superior variety. The varieties are local Tugini, local Kasmadi 1, local Kasmadi 2, local 13, local Wasis and local Miyem.